Analysis of quality of life and influence factors in patients with lung cancer undergoing radiotherapy or chemotherapy under the normalization of epidemic prevention (疫情常态化防控期间肺癌放化疗患者生活质量影响因素分析) - WU Suya (吴苏娅); WAN Jing (万晶); ZHANG Liuliu (张柳柳); WANG Min (王敏); LIU Dan (刘丹); ZHU Ping (邾萍) (Association of Integrative Nursing, 2023)
Objective To investigate the current quality of life of patients with radiotherapy and chemotherapy for lung cancer under the normalization of COVID-19 prevention, and to explore the influence factors of the quality of life in patients with radiotherapy or chemotherapy for lung cancer. Methods General information questionnaire, the Brief Fatigue Inventory(BFI), Self-Rating Anxiety Scale(SAS), Self-rating depression scale(SDS)and European organization for the research and treatment of cancer quality of life questionnaire-C30 (EORTC QLQ-C30) were used to investigate 134 patients with radiotherapy or chemotherapy for lung cancer from Jiangsu Cancer Hospital by convenience sampling method. Multiple linear regression was used to analyze the influencing factors of quality of life. Results The total quality of life in 134 patients with lung cancer was (72. 33±11. 13); Univariate analysis showed that treatment delay (t=5. 355, P<0. 001), traffic difficulty (t=2. 746, P=0. 007), adequate life security (t=3. 702, P<0. 001), clinical stage (F=50. 084, P<0. 001) and fatigue (F =2. 956, P=0. 035) were important factors affecting quality of life．Pearson correlation analysis showed that epidemic knowledge score (r=0. 179, P=0. 038) was positively correlated with quality of life, anxiety (r=-0. 551, P<0. 001) and depression (r=-0. 456, P<0. 001) were negatively correlated with quality of life. Multivariate analysis showed that clinical stage (t=-4. 880, P<0. 001), treatment delay (t =3. 158, P=0. 002), epidemic knowledge score (t =2. 019, P=0. 046) and anxiety (t =-3. 160, P=0. 002) were independent influence factors. Conclusion Under the normalization of COVID-19 prevention, the quality of life among patients with lung cancer treated by radiotherapy or chemotherapy was at a low level. Advanced clinical stage, delayed treatment, lack of epidemic knowledge and anxiety can reduce the quality of life. Patients with these factors should be provided timely and necessary intervention during clinical treatment, to improve their quality of life. (目的 调查新型冠状病毒肺炎(COVID-19)疫情常态化防控期间肺癌放化疗患者生活质量现状并分析其影响因素。方法 对2022年7月25日-8月15日江苏省肿瘤医院的134位肺癌放化疗患者进行问卷调查研究, 包括一般资料调查表、简短疲乏量表(BFI)、焦虑自评量表(SAS)、抑郁自评量表(SDS)和生活质量测定量表(EORTC QLQ-C30)。采用多元线性回归分析法分析生活质量的影响因素。结果 134位肺癌患者生活质量总分为(72. 33±11. 13)分。单因素分析显示, 治疗是否延期(t=5. 355, P<0. 001)、复诊交通是否困难(t=2. 746, P=0. 007)、生活保障是否充足(t=3. 702, P<0. 001)、临床分期(F=50. 084, P<0. 001)和疲乏程度(F=2. 956, P=0. 035)是影响患者生活质量的关联因素。Pearson 相关分析显示, 疫情知识得分(r=0. 179, P=0. 038)与生活质量呈正相关, 焦虑得分(r=-0. 551, P=0. 000)和抑郁得分(r=-0. 456, P=0. 000)与生活质量呈负相关。多元回归分析显示, 临床分期(t=-4. 880, P=0. 000)、治疗是否延期(t=3. 158, P=0. 002)、疫情知识得分(t=2. 019, P=0. 046)、焦虑(t=-3. 160, P=0. 002)为生活质量的独立影响因素。结论 疫情常态化防控期间, 肺癌放化疗患者生活质量较低, 且临床分期晚、放化疗延期、疫情相关知识不足及焦虑状态均可降低患者生活质量, 医护人员应根据其影响因素为患者提供及时、必要的干预, 提高患者生活质量, 促进疾病康复。)